PERAN KELOMPOK TANI DALAM MENINGKATKAN PENDAPATAN USAHATANI KAKAO DI DESA BOBO KECAMATAN PALOLO KABUPATEN SIGI - Nurul Syafira; Sulmi Sulmi (Fakultas Pertanian, Universitas Tadulako, 2022)
The establishment of farmer groups can simplify agricultural activities for farmers. A study was conducted in Bobo village, Palolo sub district, Sigi district with the aim of understanding cocoa farming incomes and the impact of farmer groups on cocoa farming incomes in Bobo village. The research was conducted in April and May 2021, and the location was purposefully chosen. A Simple Random Sampling method was used to select 30 sample farmers from three cocoa farmer groups. Income and Chi-Square analyses were used to analyze the data. The study discovered that the mean income for the cocoa farming was IDR 16,016.652.80/1.07Ha. The Chi-Square test demonstrated that there is a relationship between the farmer groups and the cocoa farming incomes, as H0 was rejected and H1 was approved with a Chi-Square test value of (6.99) > Chi-Square table (5.99) at 5% significant level.